Th1/Th2 Cytokine Balance and SOCS3 Levels of Female Offspring Born from Rats with Gestational Diabetes Mellitus - Sahna, Kezban Can; Risvanli, Ali (Kafkas Univ, Veteriner Fakultesi Dergisi, 2015)
Diabetes mellitus during pregnancy is a metabolic disorder that is very important in regard to both the health of the mother and the baby. We determine the effect of diabetes mellitus generated by streptozotocin with different dosages in pregnant rats on serum Th1/Th2 cytokine balance and SOCS3 levels. Twenty-one pregnant rats in their late pregnancy were used for this purpose. The rats were divided into three groups randomly and the rats in the first group were used as the control group. Streptozotocin was administered intraperitoneally at a dosage of 40 mg/kg to the rats in the second group and at a dosage of 60 mg/kg to the rats in the third group. One female offspring of each rat was decapitated and the blood of the decapitated rats was collected and Th1 [Interferon gamma (IFN gamma), Interleukin 2 (IL-2), Tumor necrosis factor alpha (TNF alpha)], Th2 [Interleukin 4 (IL-4), Interleukin 5 (IL-5), Interleukin 10 (IL-10)] cytokine levels were measured using a multiplex immunoassay based on xMAP((R)) detection technology and the suppressor of cytokine signaling 3 (SOCS3) levels were measured using a commercial ELISA kit. The IFN-gamma (1.59 +/- 0.28 pg/mL) levels in group 1 were lower than those in the other groups. The TNF-alpha (2.24 +/- 0.20, 2.21 +/- 0.19 pg/mL) levels in groups 2 and 3 were higher than in group 1, and the IL-4, IL-6, IL-10 and SOCS3 concentrations were not significantly different among groups. The SOCS3 levels of the offspring were not different among the groups, and the IFN-gamma. and TNF-a blood concentrations were increased; the Th1/Th2 cytokine balance was shifted toward Th1. We have observed that the SOCS3 levels of offspring born from mothers generated to be diabetic by administration of streptozotocin in late pregnancy were not different among various groups, and the IFN-gamma and TNF-alpha blood concentration were increased. As a result, the Th1/Th2 cytokine balance was shifted toward Th1. This suggests that more prominent cellular immunity.
Gebelikte diabetes mellitus şekillenmiş ratlardan doğan dişi yavrularda th1/th2 sitokin dengesi ve socs3 düzeyleri
Keywords: Cytokine; Diabetes Mellitus; Offspring; Pregnancy; Rat; SOCS3